The Analysis of Three Dimensions of The Main Character in Percy Jackson - Kadmaerubun, Gres Rewung; Sosiowati, I Gusti Ayu Gede; Putra, I Komang Sumaryana (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 30 No 1 (2023): Maret, 2023)
The aim of this study is to analyze the three dimensions of the main character in Percy Jackson and the Olympians: The Lightning Thief movie. The data which are used in this study are taken from a movie entitled Percy Jackson and the Olympians: The Lightning Thief. This study applied a theory proposed by Egri (1960) to analyze the three dimensions of the character and a theory proposed by Kenney (1966) to classify the method of characterization into five methods: Discursive Method, Dramatic Method, Contextual Method, Mixing Method, and Characters on the other Characters Method. The data were collected by using documentation method and note taking technique. Descriptive and qualitative method were used to analyze the data. Based on the analysis, it shows that the main character in Percy Jackson and the Olympians: The Lightning Thief movie is Percy Jackson. The findings of this study indicate that in the movie, it shows all of the three dimensions of the character. There is also method of characterization used by the author in the movie.